2012
DOI: 10.1016/j.bcp.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of breast cancer resistance protein (BCRP/ABCG2) in cancer drug resistance

Abstract: Since cloning of the ATP-binding cassette (ABC) family member breast cancer resistance protein (BCRP/ABCG2) and its characterization as a multidrug resistance efflux transporter in 1998, BCRP has been the subject of more than two thousand scholarly articles. In normal tissues, BCRP functions as a defense mechanism against toxins and xenobiotics, with expression in the gut, bile canaliculi, placenta, blood-testis and blood-brain barriers facilitating excretion and limiting absorption of potentially toxic substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
280
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(289 citation statements)
references
References 250 publications
(317 reference statements)
5
280
0
4
Order By: Relevance
“…Professional lipid ABC transporters, such as the cholesterol and phospholipid transporter ABCA1, the long-chain PC and cholesterol transporter ABCB4 (MDR3), the bile salt transporter ABCB11 (BSEP/S-P-gp), or the major sterol transporters ABCG5/G8 (working as an obligate heterodimer), have indeed been shown to be regulated by lipid-sensing NRs (Beyea et al, 2007;Jonker et al, 2009;Schmitz & Langmann, 2005;Tarling et al, 2013;van Meer et al, 2008). Interestingly, to date, several NRs also involved in the recognition of lipid ligands have been shown to affect the gene expression of human ABCB1 and ABCG2, the transport functions of which are mainly involved in causing multidrug resistance (Borst & Elferink, 2002;Jonker et al, 2009;Klaassen & Aleksunes, 2010;Natarajan, Xie, Baer, & Ross, 2012;Sarkadi et al, 2006;Scotto, 2003). Therefore, via binding to and activating their cognate NRs, lipid molecules might also be directly involved in the transcriptional regulation of both ABCB1 and ABCG2.…”
Section: P0280mentioning
confidence: 99%
“…Professional lipid ABC transporters, such as the cholesterol and phospholipid transporter ABCA1, the long-chain PC and cholesterol transporter ABCB4 (MDR3), the bile salt transporter ABCB11 (BSEP/S-P-gp), or the major sterol transporters ABCG5/G8 (working as an obligate heterodimer), have indeed been shown to be regulated by lipid-sensing NRs (Beyea et al, 2007;Jonker et al, 2009;Schmitz & Langmann, 2005;Tarling et al, 2013;van Meer et al, 2008). Interestingly, to date, several NRs also involved in the recognition of lipid ligands have been shown to affect the gene expression of human ABCB1 and ABCG2, the transport functions of which are mainly involved in causing multidrug resistance (Borst & Elferink, 2002;Jonker et al, 2009;Klaassen & Aleksunes, 2010;Natarajan, Xie, Baer, & Ross, 2012;Sarkadi et al, 2006;Scotto, 2003). Therefore, via binding to and activating their cognate NRs, lipid molecules might also be directly involved in the transcriptional regulation of both ABCB1 and ABCG2.…”
Section: P0280mentioning
confidence: 99%
“…The high expression of BCRP in tumor cells could specifically transport mitoxantrone, methotrexate, camptothecin and many anticancer drugs, forming the important cause of tumor cell resistance (Robey et al, 2009;Ni et al, 2010;Getz et al, 2011). Recent researched suggested that BCRP had protective effects on stem cell differentiation and development, and would have a large number expression in cancer stem cells Ding et al, 2010;Natarajan et al, 2012), which might provide the theoretical support of BCRP's potential overcoming the tumor resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Cai-Xia Li*, Kai Zhang, Fu-Bo Xie in cancer stem cells Ding et al, 2010;Natarajan et al, 2012), which might provide the theoretical support of BCRP's potential overcoming the tumor resistance.…”
Section: Bcrp Expression In Vx2 Rabbit Liver Tumours and Its Effects mentioning
confidence: 98%
“…In contrast to Pgp and MRP1, it contains only one NBD preceding one TMD with six membrane spanning helices (Ni et al, 2010). BCRP has been identified to have a potential impact on drug resistance in hematologic malignancies like AML and CML due to its frequent expression on malignant hematopoietic and lymphoid cells (Natarajan et al, 2012). Although several BCRP substrates are transported out of the cell at low concentrations, they are also inhibitors of BCRP at higher concentrations.…”
Section: Bcrp In Anticancer Drug Resistancementioning
confidence: 99%